Розвідки в Долинському р-ні на Кіровоградщині - Орлик, О.П. (Археологічні дослідження в Україні, 2010)
During the archaeological research in 2007—2008 on the area between the Inhul and Inhulets Rivers in Dolynska Region of Kirovohrad Oblast 99 mounds, 5 settlements of the Late Bronze Age, 2 locations (Mesolithic and Bronze Age), and a type-site (Mesolithic) were discovered. On this territory and in this region, settlements and type-sites were previously unknown.